A facile route to preparation of immobilized cellulase on polyurea microspheres for improving catalytic activity and stability. (December 2019) - Sui, Ying; Cui, Yu; Xia, Guangming; Peng, Xiujing; Yuan, Guangzheng; Sun, Guoxin
Highlights: Uniform, monodisperse polyurea microspheres were successfully prepared. Cellulase was covalently immobilized on polyurea microspheres. The immobilized cellulase exhibited more stability and higher activity. The activity of cellulase could be improved by trace amounts of dimethyl sulfoxide. Graphical abstract: Abstract: The input-output ratio of the immobilization process is crucial to determining whether the immobilized cellulase can truly participate in industrial production. This study reports a simple, efficient and environmentally friendly method for covalent immobilization of cellulase on uniform, monodisperse polyurea microspheres. The reported method offers several benefits including (i) polyurea microspheres can be obtained after one step reaction without any shaking or stirring at room temperature, (ii) Without any modification, the surface of polyurea microspheres contains abundant amine groups for immobilized cellulase, (iii) Compared with porous materials, cellulase was immobilized on the surface of the support, leading to less mass transfer resistance during immobilization and catalytic reaction. The support and immobilized cellulase were characterized by SEM, TEM, AFM, FT-IR, TGA. The immobilized cellulase demonstrated a high recovery of activity (77.9%) and showed improved thermostability, pH tolerance, reusability and lifetime. Notably, the immobilized cellulase exhibited a superior performance after 36 h in the continuous process. More interestingly, trace amounts of dimethyl sulfoxide was found to promote cellulase activity. This work provides a simple and practically method for promising applications as biocatalyst in cellulose hydrolysis and an effective strategy for the immobilization of other enzymes in green chemical industry.